The influence of patient sex on clinical approaches to malignant glioma. (1st January 2020) - Matteoni, Silvia; Abbruzzese, Claudia; Villani, Veronica; Malorni, Walter; Pace, Andrea; Matarrese, Paola; Paggi, Marco G.
Abstract: Gliomas are tumors that originate from the glial tissue, thus involving the central nervous system with varying degrees of malignancy. The most aggressive and frequent form is glioblastoma multiforme, a disease characterized by resistance to therapies, frequent recurrences, and extremely poor median survival time. Data on overall glioma case studies demonstrate clear sex disparities regarding incidence, prognosis, drug toxicity, clinical outcome, and, recently, prediction of therapeutic response. In this study, we analyze data in the literature regarding malignant glioma, mainly glioblastoma multiforme, focusing on epidemiological and clinical evaluations. Less discussed issues, such as the role of viral infections, energy metabolism, and predictive aspects concerning the possible use of dedicated therapeutic approaches for male or female patients, will be reported together with different estimated pathogenetic mechanisms underlying astrocyte transformation and glioma chemosensitivity. In this era, where personalized/precision medicine is the most important driver for targeted cancer therapies, the lines of evidence discussed herein strongly suggest that clinical approaches to malignant glioma should consider the patient's sex. Furthermore, retrospectively revising previous clinical studies considering patient sex as a crucial variable is recommended. Highlights: Malignant gliomas and, in particular, glioblastoma are severe forms of brain cancers. These cancers display clear sex-related disparities regarding incidence and clinical course. In addition to epidemiological data, molecular findings demonstrate sex disparities in malignant glial tumors. In personalized medicine, a sex-specific evaluation should be considered when treating patients with malignant gliomas.